The role of comparison sites and image features in consumer search - KOH, Peng Yam (Institutional Knowledge at Singapore Management University, 2021)
Comparison sites are widely used by consumers. Theory assumes that consumers visit these sites to discover new alternatives, raising questions about the role of the initial consideration set (alternatives considered at the start of search) when comparison sites are available. Will consumers ignore their initial consideration set and directly explore new alternatives? Will consumers with large initial consideration sets avoid comparison sites? Utilizing search and incomplete knowledge theories, the authors intuit that consumers first search their initial consideration set, and visit a comparison site to reduce the search costs of doing so. If a suitable alternative is absent, consumers subsequently visit a comparison site to discover new alternatives. The authors test their expectations on unique data capturing consumers’ initial consideration sets and online search and find strong support. Specifically, consumers search a greater proportion of their initial consideration set at the start of search and are more likely to visit a comparison site when their initial consideration set is large. Additionally, consumers are more likely to visit a comparison site when they expect to find a better deal, particularly at the end of search. Finally, only consumers expecting to find a better deal are more likely to explore alternatives not in their initial consideration set.